The Effects of Differentiated Instruction in an Online Classroom on the Levels of Willingness to Communicate of Thai EFL Undergraduates - Rattanasaeng, Kanpajee; Bunsorn, Maliwan (Arts of Management Journal, 2024)
This article aimed to study (1) the needs of students in the Foundation English 1 course in an online classroom regarding their interests in topics and the learning styles of the students, and (2) the effects of differentiated instruction in an online classroom on the levels of willingness to communicate in English. The sample group consists of 30 students who enrolled in Foundation English 1 but are not English major students. The sampling method used is simple random sampling. These students are from an educational institution in Bangkok from the third semester of the academic year 2022. The research tools used in this study include a needs analysis questionnaire to identify needs, lesson plans, a willingness to communicate questionnaire in the Linkert scale, and semi-structured interviews. The data were analyzed by using Mean, Standard Deviation (SD) values, a Paired Sample T-Test to compare the pre-test and post-test, and content analysis applied to interview results. The results indicated that students’ interests in lesson topics, including self-introduction, eating out, traveling, and fashion, in terms of learning styles exhibit characteristics of images, symbols, and sounds. The pre-test mean score was 2.08, SD = 0.97 which indicated a low level of willingness to communicate. The post-test mean score was 3.80, SD = 0.94, which indicated a high level of willingness to communicate. When comparing the means using the Paired Sample T-Test, it was found that there was a statistically significant difference at the .05 level. This research suggests that the findings can be utilized as a guideline for designing English lessons aiming at developing a willingness to communicate, thus assisting in enhancing speaking skills in the future.